Data Collection in Zooarchaeology: Incorporating Touch-Screen, Speech-Recognition, Barcodes, and GIS - W. Flint Dibble (Ethnobiology Letters, 2015)
When recording observations on specimens, zooarchaeologists typically use a pen and paper or a keyboard. However, the use of awkward terms and identification codes when recording thousands of specimens makes such data entry prone to human transcription errors. Improving the quantity and quality of the zooarchaeological data we collect can lead to more robust results and new research avenues. This paper presents design tools for building a customized zooarchaeological database that leverages accessible and affordable 21st century technologies. Scholars interested in investing time in designing a custom-database in common software (here, Microsoft Access) can take advantage of the affordable touch-screen, speech-recognition, and geographic information system (GIS) technologies described here. The efficiency that these approaches offer a research project far exceeds the time commitment a scholar must invest to deploy them.